Special endurance of young gymnasts: The role of aerobic capacity in fatigue development in the training - Sawczyn, S.; Biskup, L.; Zasada, M.; Mishchenko, V. (Central European Journal of Sport Sciences and Medicine, 2018)
In artistic gymnastic alteration of all component of coordination capacities may related to fatigue. So the resistance to fatigue is a specific endurance component, which has direct relation to the techniques of gymnastic exercises. We supposed that changes of motor actions precise in the process of fatigue development during training sessions might presumably have a negative impact on the quality of performing complex gymnastic elements and combinations and set the goal to determine the significance level of aerobic capacity for special endurance. Twelve young skilled gymnasts aged 15-18 years measured the maximum oxygen consumption (VO2 max). During the training sessions specially designed tests of specific endurance were carried out, heart rate (HR) was measured and the quality of the presentation of the combinations was evaluated (by the sum of the judges' ratings of all the elements). The interrelation between VO2 max, HR in progress of gymnastic combinations and the quality of their performance were analyzed. Results showed that a higher aerobic capacity contributes to a relatively lower HR when performing intense gymnastic combinations and a slower development. Iof "coordination fatigue" t may be of special importance for young athletes at the stage of advanced specialization when a great volume of complex combinations is learned and thus, high volume of training loads is performed. According to obtained data use of the proposed endurance tests is of great importance for control of maintenance of aerobic capacities by young athletes. Account of the factors of "coordination fatigue" development, related to aerobic capacities, may be of special importance for young gymnasts at the stage of advanced specialization when a great volume of complex combinations is learned and thus, high volume of training loads is performed.